Ovary transcriptomic analysis reveals regulation effects of dietary fish oil on hormone, lipid, and glucose metabolism in female adult spotted scat (Scatophagus argus) - Wang, Tuo; Liu, Zhi-Long; Li, Guang-Li; Mustapha, Umar Farouk; Ndandala, Charles Brighton; Shi, Hong-Juan; Zhu, Chun-Hua; Chen, Hua-Pu; Huang, Yang; Jiang, Dong-Neng (Frontiers in Marine Science, 2022)
In the aquaculture industry, fish oil is widely used as a nutritional supplement to promote the gonadal maturation of broodstocks, while the mechanism of fish oil on ovary development remain unclear. Herein, female adult spotted scat (Scatophagus argus) with most ovaries at phase II were fed with diets containing 8% soybean oil (SO) or 8% fish oil (FO) for 60 days. The final average fish body weight was similar between FO and SO groups. The average gonadosomatic index (GSI) of FO group was higher (non-significant) than that of SO group. Finally, the phase IV ovary of the FO and SO groups were 7 and 5 out of 10, respectively. The serum estradiol (E2) level of the FO group was significantly higher than that of the SO group. The proportions of n-3 long-chain polyunsaturated fatty acids (LC-PUFA, such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA)) in the ovaries were much higher in the FO group than in the SO group. These results suggest that the maturity level of the FO group is relatively higher than that of the SO group. Transcriptome sequencing was used to detect the ovary gene expression. Comparatively, the ovary transcriptome analysis showed 68 up-regulated and 193 down-regulated genes in the FO group. The expression levels of Jund and Jun necessary for the ovary maturation were up-regulated in the FO group, while Pparγ and Cxcl12, which could inhibit the ovary development, were down-regulated in the FO group. Cyp3a27 coding the enzyme for degrading the estrogen was significantly down-regulated in the FO group and coincided with the increase of its serum E2. Kif5b which could regulate the glucose metabolism was up-regulated in the FO group. Serum insulin level was also increased in the FO group. Additionally, Aldh3a2 and Plin2 related to lipid metabolism were significantly down-regulated in the FO group. Briefly, dietary fish oil can influence the expression of genes related to steroid hormone, glucose and lipid metabolism. This study will clarify the mechanism of dietary fish oil in promoting ovary development in teleost fish.